Advances in atomic, molecular, and optical physics. - Arimondo, E.; DiMauro, Louis; Yelin, Susanne F. (Academic Press, 2018)
Advances in Atomic, Molecular, and Optical Physics, Volume 67, provides a comprehensive compilation of recent developments in a field that is in a state of rapid growth. Topics covered include related applied areas, such as atmospheric science, astrophysics, surface physics, and laser physics, with timely articles written by distinguished experts that contain relevant review materials and detailed descriptions of important developments in the field.